PENGARUH METODE PEMBELAJARAN EKSPERIMEN TERHADAP PENINGKATAN HASIL BELAJAR SISWA (Studi Eksperimen di Kelas VII SMP pada Konsep Energi dalam Sistem Kehidupan) - Dina Rahmawati; Adi Maladona; Aden Arif Gaffar (Universitas Majalengka, 2018)
Abstract This research purposed to know the influences of student learning result in 7th grade The First Public Junior High School Ciamis on the Energy in Living Systems concept. The research was conducted from 29 November 2013 to 1 March 2014. The population in this study were all classes in 7th grade The First Public Junior High School Ciamis which consists of 9 classes as much as 337 student. The samples used in this research were 2 classes taken using cluster random sampling technique, which VII D and VII E. Instrument that used in this study is achievement test on the Energy in Living Systems concept, form multiple choice with four option as much as 50 question. Data analysis techniques used by t test. The result researching at the experiment class pointed that pre test = 8,87 and post test = 22,19, where was at the control class pre test = 9,47 and post test = 10,84. The median score was determined is 22,5, as for the real of median scores= 25 and control class=